2017
DOI: 10.1111/anae.13905
|View full text |Cite
|
Sign up to set email alerts
|

The height of the cricothyroid membrane on computed tomography scans in trauma patients

Abstract: SummaryEmergency cricothyrotomy is a common feature in all difficult airway algorithms. It is the final step following a 'can't intubate, can't oxygenate' scenario. It is rarely performed and has a significant failure rate. There is variation in the reported size of the cricothyroid membrane, especially across population groups. Procedural failure may result from attempting to pass a device with too large an external diameter through the cricothyroid membrane. We aimed to determine the maximum height of the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 7 publications
(10 reference statements)
5
25
0
Order By: Relevance
“…Novel tools are enhancing our understanding of airway anatomy , and this study is a contribution to the increasing body of evidence that challenges current widely held views on airway management. If cricoid pressure is deemed to be beneficial, the cricoid cartilage should be located using the best available techniques, and without compromising patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…Novel tools are enhancing our understanding of airway anatomy , and this study is a contribution to the increasing body of evidence that challenges current widely held views on airway management. If cricoid pressure is deemed to be beneficial, the cricoid cartilage should be located using the best available techniques, and without compromising patient safety.…”
Section: Discussionmentioning
confidence: 99%
“…A second issue was raised in a study which suggested that a 6.0-mm tracheal tube may be too big to fit through the CTM [5]. Although this study provided the largest series of measurements to date, the height of the CTM was measured from scans of patients with the head and neck in a neutral position.…”
Section: Introductionmentioning
confidence: 99%
“…CT is expected to be more precise than the US and palpation method, because CT imaging is considered to be an omnipresent feature reflecting the precise anatomy of CTM. [10] Therefore, this study compares and validates the palpation and US method against the commonly used technique, i.e., CT scan, for the first time to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 93%
“…[7] However, the clinical efficacy of the US guidance to identify the CTM is unclear compared to computed tomography (CT), which is a commonly used radiological technique and allows an accurate identification of the airway structures. [10] The aim of this prospective clinical study was to investigate the success rates of US and conventional finger palpation methods in identifying the cricothyroid membrane (CTM) and comparing the precision of identifying the CTM against the commonly used radiological technique-the CT scan. The time taken to assess CTM using the US and finger palpation methods and the difficulty of using these methods and factors associated with the success rates while determining the CTM localization were the secondary outcomes.…”
Section: Introductionmentioning
confidence: 99%